2008
DOI: 10.1179/174328508x283469
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for smelting of chromite ore, pellets, briquettes and sinter

Abstract: Ferrochrome (.62%Cr) and charge chrome (45-52%Cr) production using the submerged arc furnace (SAF) is an established practice in India. As the majority of Cr rich Indian chromite ore are friable in nature and available in fine form, utilisation of chromite fines for production of superior quality ferrochrome is essential. For this purpose, in the present study, the smelting of chromite pellets, briquettes, sinter and lump ore has been carried out in an electric arc furnace of 50 kVA. The energy consumption, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…5. And it can be inferred that for reduction of chromite reaction (3) starts from 1 456 K and reaction (7) starts from 1 301 K (point c), which are much higher than that of iron ore with starting reduction temperature of 992 K for reaction (3) and 1 031 K (point b) for reaction (6). Carbon monoxide reduction of iron in iron ore and chromite is also highly correlated with equilibrium vapor composition.…”
Section: Enhancement Mechanism Of Chromite Reduction In Prereduced Comentioning
confidence: 94%
See 1 more Smart Citation
“…5. And it can be inferred that for reduction of chromite reaction (3) starts from 1 456 K and reaction (7) starts from 1 301 K (point c), which are much higher than that of iron ore with starting reduction temperature of 992 K for reaction (3) and 1 031 K (point b) for reaction (6). Carbon monoxide reduction of iron in iron ore and chromite is also highly correlated with equilibrium vapor composition.…”
Section: Enhancement Mechanism Of Chromite Reduction In Prereduced Comentioning
confidence: 94%
“…And the prereduced pellets are proved better than traditional "lumpy ore" because they can contribute to lower energy consumption in furnace and better metallurgical properties. [5][6][7] However, chromite ores have extremely high soften-melting temperature, normally more than 1 823 K (increases with the total content of MgO and Al2O3), which may make BF operations difficult. 2,7) Therefore, in order to reduce the melting point of the burden, a mixture of chromite concentrate and iron ore is utilized as feed material to produce prereduced pellets and the coal-based direct reduction process is widely adopted because China is seriously short of natural gas resources but has vast indigenous reserves of reducing coal.…”
Section: Introductionmentioning
confidence: 99%
“…Sinter being porous in nature may have lower thermal conductivity than the lump ore resulting in poor heat transfer from the arc during the initial stage. 17 It has been observed that, for lump ore, a liquid pool was formed beneath the electrodes within 5-7 min of arcing, in comparison to 10-15 min for sinter. This may facilitate early direct heating for lumps by submerged arcing.…”
Section: Comparison Of Chromite Sinter and Lump Ore Smelting Study In...mentioning
confidence: 99%
“…Sintering of chromite ore fines were carried out by Zhu et al 15 and found incipient formation of 20% liquid phase (olivine) in the produced sinter, which shows 70.6% sinter yield and 57.27% tumbler index. Other investigators 16,17 also studied on sintering of chromite ore fines and their performance in smelting in a laboratory scale electric arc furnace (EAF). They showed that the specific power consumption in the melting was comparable with that of the heat hardened chrome ore pellets and lower than the briquettes and lump ores.…”
Section: Introductionmentioning
confidence: 99%